2019
DOI: 10.18552/2019/idscmt5186
|View full text |Cite
|
Sign up to set email alerts
|

Exploring challenges of adopting sustainability assessment: Methods in UAE - Perspectives of project professionals

Abstract: UAE's sustainable construction industry is expanding with increased interest in promoting green buildings while addressing global environmental concerns. However, it has been established that the effectiveness of implementing building environmental sustainability assessment methods varies significantly with several variables. While, a substantial body of literature has focused on the development of rating systems, less is known about the barriers and challenges of adopting the current assessment methods in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…To have more depth in the circular economy policy in EU, guidelines for supply efficiency, integrating elements of Circular Economy, can be dated back to the 1980s and 1990s in German structured policymaking, essentially prejudiced by the captivating then-new notion of the closed-loop economy (Shibieka et al, 2019). For example, as a result of that, during the last 20 years, the strategic resource plan track of EU progressively moved towards the sustainable usage of natural capital, increasing supply effectiveness in the business economy, and encouraging the recovering and prevention of industrial by products, while at the same time it supports the economic growth movement as shown in Fig 3 . On the other hand, the policy scholars see that the circular economy policy could have another classification than the one illustrated in Fig.…”
Section: Circular Economymentioning
confidence: 99%
“…To have more depth in the circular economy policy in EU, guidelines for supply efficiency, integrating elements of Circular Economy, can be dated back to the 1980s and 1990s in German structured policymaking, essentially prejudiced by the captivating then-new notion of the closed-loop economy (Shibieka et al, 2019). For example, as a result of that, during the last 20 years, the strategic resource plan track of EU progressively moved towards the sustainable usage of natural capital, increasing supply effectiveness in the business economy, and encouraging the recovering and prevention of industrial by products, while at the same time it supports the economic growth movement as shown in Fig 3 . On the other hand, the policy scholars see that the circular economy policy could have another classification than the one illustrated in Fig.…”
Section: Circular Economymentioning
confidence: 99%
“…Relevant research has found that decisions made early in the design stage affect the building's performance during operation [1], and integration of design, engineering and construction is key for the development and delivery of sustainable, high-performance buildings [2]. Yet, integration of engineering disciplines remains as one of the main challenges when adopting environmental sustainability assessment methods [3]. Hence, research and practice concerned with sustainability of the built environment are required to focus on investigating the role of design and integration in the environmental impacts across the life cycle of a building.…”
Section: Introductionmentioning
confidence: 99%